Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 2 - P.S. Problem Solving - Page 239: 9c


$f^{-1} (x)=\dfrac{x}{4}$ and $g^{-1} (x)=x-6$

Work Step by Step

Interchange $x$ and $y$: $x=4y $ $\implies y=\dfrac{x}{4}$ Replace $y$ with $f^{-1} (x)$ or, $f^{-1} (x)=\dfrac{x}{4}$ Replace $g(x)$ with $y$. $ g(x) =x+6$ Interchange $x$ and $y$: $x=y+6 $ so, $y=x-6 \implies g^{-1} (x)=x-6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.